Epidemiology of Childhood Trauma and Analysis of Influencing Factors in Psychiatric Disorders Among Chinese Adolescents: A Cross-sectional Study. Issue 19 (October 2022) - Liu, Jianbo; Lin, Xiujin; Shen, Yanmei; Zhou, Yuanyue; He, Yuqiong; Meng, Tiantian; Cui, Xilong; Xiao, Bo; Lu, Jianping; Zhang, Xiangyang; Luo, Xuerong
Childhood trauma (CT) can lead to long-term psychiatric disturbances. The current study investigated the prevalence of CT and its associated risk factors among Chinese adolescents with psychiatric disorders. Adolescents were recruited from a large study on mental health in the Hunan province of China in 2014. The study had a two-phase cross-sectional design. Patients with mental disorders (n = 907) and healthy subjects (n = 2, 240) completed the Childhood Trauma Questionnaire–Short Form. Of all types of CT, emotional neglect (EN; 48.44%-68.82%) and physical neglect (PN; 60.0%-72.1%) were most common among adolescents. The experience of emotional abuse (EA), physical abuse (PA), sexual abuse (SA), EN, and multiple types of trauma (≥3) was higher among adolescents with psychiatric disorders than the healthy comparison group. Moreover, the results of logistic regression analysis showed that living in semi-urban areas and villages, having a sibling, and having bad-to-average academic performance were risk factors for CT among adolescents with psychiatric disorders ( p < .05). In additional, the results of logistic regression analysis revealed that being a left-behind child and bad academic performance were risk factors for experiencing multiple types (≥3) of CT ( p < .05), while being female and having siblings were found to be protective factors against (≥3) CT ( p < .05). In summary, the prevalence rate of CT (especially multiple types of trauma) is high among adolescents with psychiatric disorders. These results indicate the importance of reducing CT to limit the likelihood of psychiatric disorders, especially among adolescents.